IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK DALAM KEBIJAKAN MERDEKA BELAJAR DI KABUPATEN PANDEGLANG - Dinta Nurachma; Arenawati, Arenawati (LPPM STIA Banten, 2024)
One of Merdeka Belajar's products is the Driving School Program. In principle, the Driving School aims to improve the quality of education in Indonesia, and this Driving School is a program that focuses on developing student learning outcomes holistically through realizing and focusing on learning based on the Pancasila student profile. Driving schools have characteristics that are in accordance with the characteristics of the Education Policy. In its implementation, the Driving School Program in Pandeglang Regency encountered various problems such as the lack of a role for supervisors at driving schools in developing and improving school resources, lack of outreach and support from the local government and budget limitations which hampered program implementation. The aim of this research is to determine the implementation of the Driving School Program in the Independent Learning Policy in Pandeglang Regency. The theory used is the theory of George C. Edward III. This research uses descriptive qualitative methods. The data collection techniques used were interviews, observation and documentation. The results of the research show that the implementation of the Mobilizing School Program in Pandeglang Regency has not proceeded according to the existing objectives because efforts are still needed to resolve these problems starting from ongoing communication between all parties concerned. Adequate resources, and the readiness or attitude of policy implementers so that the driving school program policy is implemented in accordance with the rules and is carried out well.